1986
DOI: 10.1210/endo-118-1-312
|View full text |Cite
|
Sign up to set email alerts
|

Superior Efficacy of PulsatileVersusContinuous Hormone Exposure on Hepatic Glucose Productionin Vitro*

Abstract: To elucidate the potency of continuous vs. intermittent exposure to hormonal stimuli, hepatic glucose production of isolated perfused rat livers was monitored in response to glucagon and insulin infusion. Using a nonrecirculating perfusion system, continuous exposure to glucagon (35 pM) induced a rise in hepatic glucose production from basal 0.33 +/- 0.03 mmol/(96 min X 100 g BW) to 0.65 +/- 0.02 mmol/(96 min X 100 g BW), while intermittent exposure (3 min on/off intervals; total dose 50%) to the same glucagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
2
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 30 publications
1
59
2
1
Order By: Relevance
“…n humans and animals, insulin secretion is pulsatile, and this pulsatility is advantageous for insulin action on its target tissues (1)(2)(3). Furthermore, pulsatile insulin secretion is disrupted in type 2 diabetes, with reduction in the amplitude and possibly frequency of the insulin pulses in diabetic patients (4 -6) and their close relatives (7,8).…”
mentioning
confidence: 99%
“…n humans and animals, insulin secretion is pulsatile, and this pulsatility is advantageous for insulin action on its target tissues (1)(2)(3). Furthermore, pulsatile insulin secretion is disrupted in type 2 diabetes, with reduction in the amplitude and possibly frequency of the insulin pulses in diabetic patients (4 -6) and their close relatives (7,8).…”
mentioning
confidence: 99%
“…In addition, insulin action is markedly impaired in diabetes and prediabetes [44]. The impaired pulsatile insulin release has been linked to impaired insulin action [4,5,6,7] but the causes and implications need to be fully established. Mechanistic studies in animal models are an important tool for evaluating this relation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This problem can, to some extent, be circumvented by studying first degree relatives of diabetic patients who are at risk of the disease but are still not affected by the effects of hyperglycaemia [9]. However, animal models are a valuable research tool for examining the relation between beta-cell mass, function and morphology on the one hand and insulin It is well documented that insulin concentrations show large amplitude oscillations in the peripheral circulation with a periodicity of 5 to 15 min [1,2,3], and it has been shown that these oscillations are of importance for insulin action in liver [4], muscle [5,6] and adipose tissues [7]. Since Type II (non-insulin-depenresistance on the other, because carefully controlled studies can involve surgical [10,11,12] or toxicological [10,13,14,15,16,17] induction of diabetes and long-term maintenance on experimental diets can induce insulin resistance and lipotoxicity [18,19,20,21].…”
mentioning
confidence: 99%
“…4 Importantly, secretory pulses are more effective than constant insulin levels in lowering plasma glucose levels. 3,5,6 In particular, hepatic signaling is highly sensitive to whether insulin is released in pulses, 7 leading to the suggestion that insulin resistance in the liver is secondary to disturbed pulsatile insulin release. 8 Thus, a deeper understanding of oscillatory b-cell activity and its disturbance has clinical relevance.…”
Section: Introductionmentioning
confidence: 99%